Revealing Homo Donans: Liberating the Unilateral Gift from Commodity Exchange - Vaughan, Genevieve (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2020)
The nurturing of the infant from birth onwards provides an example of unilateral gift giving made necessary by the helplessness of the child who cannot exchange an equivalent for what she is given. This material transaction, the giving and receiving of goods and care, creates basic interpersonal schemas of material communication, which underlie verbal communication. They differ from the schemas created by quid pro quo exchange. The market economy is composed of both types of transactions, but unilateral gifts are given to and taken by the exchange transaction mechanism in order to create profit. Reinterpreting maternal care as a free communicative economy points towards a redefinition of the human as Homo Donans and provides a way out of the end of the world scenario to which capitalism has brought us. Using ideas of Marx, Vygotsky, Rossi-Landi, Sohn-Rethel, Lakoff, the findings of recent infancy research, interpersonal neurobiology and modern matriarchal (Goettner-Abendroth) and matricentric (O’Reilly) feminism, I propose a radical shift towards the gift paradigm.